Entrepreneurial Literacy at the Higher Education after Covid-19 Pandemic: Systematic Literature Review (SLR) - Dyah Ayu Fitriastuti; Agus Salim; Lailatul Rohmah; Aniek Indrawati; Ludi Wishnu Wardana (Brilliant International Journal Of Management And Tourism, 2023)
After the Covid-19 pandemic, many economies were paralyzed, especially business actors who had difficulty starting to get up. This crisis is caused by the corona virus, so society needs to examine measures to protect the health and economic consequences, protect vulnerable populations, and set the stage for economic recovery through entrepreneurship. The purpose of this study was to find out the portrait of entrepreneurial literacy at the tertiary level. The method used in this research is Systematic Literature Review (SLR) by collecting and analyzing journals related to keywords. Based on the literature study conducted, it was found that entrepreneurial literacy at the tertiary level is now up to date and is expanding from conventional to digitalization. The more sophisticated technology owned by each student can increase the chances of becoming an entrepreneur. The results of this research have implications for three things: First, universities are expected to continue to upgrade entrepreneurship learning in a creative, innovative and adaptive manner. Second, the government is expected to continue to improve technology facilities evenly and improve mentoring/training programs for business actors. The third is for business actors to continue to be open minded in accepting all changes that can be used to survive in entrepreneurship.